Magnetic-field induced dimensionality switch of charge density waves in strained 2H-NbSe2 surface - Ryo Ichikawa; Yukiko K. Takahashi; Eiichi Inami; Toyo Kazu Yamada (npj 2D Materials and Applications)
Abstract Thinning van der Waals crystals to monolayers is crucial for nanoelectronic devices but often introduces strain, altering their electronic properties. This study explores how strain affects the charge density wave (CDW) in 2H niobium diselenide (2H-NbSe2), focusing on a transition from a 2 × 2 to a 1Q CDW phase under weak magnetic fields (~30 mT), revealing high magnetic sensitivity. The strained 2H-NbSe2 surface, prepared via vacuum and tape exfoliation, exhibits a 2 × 2 CDW phase observed using low-temperature (4.3 K) scanning tunneling microscopy and spectroscopy (STM/STS) combined with scanning electron microscopy (SEM) and cross-sectional transmission electron microscopy (TEM) under ultrahigh vacuum (UHV) conditions. STS maps show the 2 × 2 CDW around ±100 meV from the Fermi level. Upon applying a magnetic field, a localized 1Q stripe CDW pattern emerges near ±40 meV. These results highlight the influence of strain and magnetic fields on CDW behavior in 2D materials.